FDI and superstar spillovers: Evidence from firm-to-firm transactions - Mary Amiti; Cédric Duprez; Jozef Konings; John Van Reenen (National Bank of Belgium, 2023)
Despite competition concerns over the increasing dominance of global corporations, many argue that productivity spillovers from multinationals to domestic firms justify pro-FDI policies. For the first time, we use firm-to-firm transaction data in a developed country to examine the impact of forming a new relationship with a multinational, and find a TFP increase of about 8% three or more years after the event. Sales to other buyers, trade and customer quality also increase. However, we also document that starting to supply other "superstar firms" such as those who heavily export or are very large also increases performance by similar amounts, even if the superstar is a non-multinational. Placebos on starting relationships with smaller firms and novel identification strategies relying solely on demand shocks to superstar firms support a causal interpretation. A model of technology transfer rationalizes these effects and also correctly predicts (i) falls in post-event markups; (ii) the type of firms who form superstar relationships and (iii) bigger treatment effects from superstars intensive in R&D, IT and/or human capital. In addition to productivity spillovers, we document the transmission of "relationship capabilities" and "dating agency" effects as the increase in new buyers is particularly strong within the superstar firm's existing network. These results suggest an important role for raising productivity through the supply chains of superstar firms regardless of their multinational status.
Keywords: F23; O30; F21; 330; Productivity; FDI; spillovers; Multinationales Unternehmen; Auslandsinvestition; Lieferkette; Industrieforschung; Technologietransfer; Spillover-Effekt